NUMERICAL SIMULATION OF HUMAN BLOOD FLOW IN MICROVESSELS - Ullah, Atta; Chughtai, I. R.; Nadeem, M. (The Nucleus, 2020)
In this research, steady state flow of human blood in vascular system has been studied. Computational fluid dynamics has been used to predict pressure drop in human arteriole, artery, capillary, venule and vein. Viscosity of human blood has been treated in different ways by employing Newtonian, Power law and Herschel-Bulkley models. It has been observed that the Herschel-Bulkley model predicts the pressure gradients in all diameters reasonably whereas Newtonian and Power laws have their limitations.